Metaplastic Breast Carcinoma Versus Triple-Negative Breast Cancer: Survival and Response to Treatment. Issue 52 (December 2015) - Aydiner, Adnan; Sen, Fatma; Tambas, Makbule; Ciftci, Rumeysa; Eralp, Yesim; Saip, Pinar; Karanlik, Hasan; Fayda, Merdan; Kucucuk, Seden; Onder, Semen; Yavuz, Ekrem; Muslumanoglu, Mahmut; et al.
Abstract : Abstract: Metaplastic breast carcinoma (MBC) differs from classic invasive ductal carcinomas regarding incidence, pathogenesis, and prognosis. The purpose of this study was to compare patients with MBC with clinicopathologic and treatment-matched patients with triple-negative breast carcinoma (TNBC) in terms of response to treatment, progression, and survival. Fifty-four patients with MBC and 51 with TNBC, who were treated at Istanbul University, Institute of Oncology, between 1993 and 2014, were included in the study. After correctly matching the patients with 1 of the 2 groups, they were compared to determine differences in response to treatment, disease progression, clinical course, and survival. At a median follow-up of 28 months, 18 patients (17.1%) died and 27 (25.5%) had disease progression. Metaplastic histology was significantly correlated with worse 3-year progression-free survival (PFS) (51 ± 9% vs. 82 ± 6%, P  = 0.013) and overall survival (OS) (68 ± 8% vs. 94 ± 4%, P  = 0.009) compared with TNBC histology. Patients who received taxane-based chemotherapy (CT) regimens or adjuvant radiotherapy had significantly better PFS ( P  = 0.002 and P  < 0.001) and OS ( P  < 0.001 and P  < 0.001) compared with others. In the multivariate analysis, MBC (hazard ratio [HR]: 0.09, P  < 0.001), presence of neoadjuvant chemotherapy (NACT) (HR: 12.8, P  = 0.05), and metastasis development at any time during the clinical course (HR: 38.7, P  < 0.001) were significant factors that decreased PFS, whereas metastasis development was the only independent prognostic factor of OS (HR: 23.8, P  = 0.009). MBC is significantly correlated with worse PFS and OS compared with TNBC. Patients with MBC are resistant to conventional CT agents, and more efficient treatment regimens are required.